Membangun Kepercayaan: Peran LPS Syariah dalam Menjaga Stabilitas Perbankan Syariah - Rifni Miftahur Rohmah; Isna Farikh Nuzula; Romziyeh (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The monetary crisis in Indonesia in 1998 resulted in the liquidation of 16 banks so that people did not trust banks. Even though banking is an important component in the national economy. Overall economic stability is influenced to a large extent by banking conditions. LPS is here as a solution to this problem. This is based on Presidential Decree no. 26 of 1998 concerning guarantees for payment obligations of commercial banks and Presidential Decree no. 193 of 1998 regarding guarantees for payment obligations of rural credit banks. The aim of this research is to better understand by knowing specifically the role of LPS in maintaining the stability of sharia banking. The research method used is descriptive qualitative research. The results of this research state the important role of LPS in maintaining bank stability. An unstable financial system can cause the economy to be disrupted, while the process of recovering an unstable economic system requires very high costs and a long time to restore public confidence in the financial system and banking system. The existence of LPS can have an effect on anticipating these risks by guaranteeing bank customers' deposits and carrying out settlements or handling of failed banks so that customers' trust in the bank is restored.